A detailed study on Sn4+ doped ZnO for enhanced photocatalytic degradation - Beura, Rosalin; Pachaiappan, R.; Thangadurai, P. (Applied surface science, 2018)
[Display omitted] •Sn ion doped ZnO for varying doping % (1, 5, 10, 15, 20, 30) was synthesized by chemical method.•Structural, optical and electrical properties were studied in detail.•Photocatalytic studies showed that upto 99 % of methyl orange was degraded under UV light.•Optimum doping % for the best photo degradation was obtained to be 1%.•Lower bandgap, increased PL lifetime and increased charge transfer have resulted in enhanced photodegradation. The samples of Sn4+ doped (1, 5, 10, 15, 20 & 30%) ZnO nanostructures were synthesized by a low temperature hydrothermal method. Structural analysis by XRD and Raman spectroscopy showed the hexagonal wurtzite phase of ZnO and the formation of a secondary phase Zn2SnO4 beyond 10% doping of Sn4+. Microstructural analysis by TEM also confirmed the wurtzite ZnO with rod as well as particle like structure. Presence of various functional groups (OH, CH, ZnO) were confirmed by FTIR. Optical properties were studied by UV–vis absorption, photoluminescence emission spectroscopies and lifetime measurement. Band gap of the undoped and Sn4+ doped ZnO were analyzed by Tauc plot and it was observed that the band gap of the materials had slightly decreased from 3.2 to 3.16eV and again increased to 3.23eV with respect to the increase in the doping concentration from 1 to 30%. A significant change was also noticed in the photoluminescence emission properties of ZnO i.e. increase in the intensity of NBE emission and decrease in DLE, on subject to Sn4+ doping. Average PL lifetime had increased from 29.45ns for ZnO to 30.62ns upon 1% Sn ion doping in ZnO. Electrical properties studied by solid state impedance spectroscopy showed that the conductivity had increased by one order of magnitude (from 7.48×10−8 to 2.21×10−7S/cm) on Sn4+ doping. Photocatalytic experiments were performed on methyl orange (MO) as a model industrial dye under UV light irradiation for different irradiation times. The optimum Sn4+ content in order to achieve highest photocatalytic activity was found to be 1% Sn 4+ doping. The enhancement was achieved due to a decrease in the band gap favoring the generation of electron-hole pairs and the enhanced PL life time that delays the recombination of these charge carrier formation. The third reason was that the increased electrical conductivity that indicated the faster charge transfer in this material to enhance the photocatalytic activity. The Sn doped ZnO was found to be more photostable than pure ZnO.